Young Adults’ Short-Term Trajectories of Moderate Physical Activity: Relations With Self-Evaluation Processes - Garn, Alex C.; Simonton, Kelly L. (Frontiers in Psychology, 2020)
Young adults face numerous barriers that can undermine their engagement in healthy behaviors. For example, young adults on average experience disproportionally large declines in physical activity participation compared to other demographic groups. Self-evaluation processes may help explain these declines. This study investigated young adults’ weekly trajectories of moderate physical activity, exploring self-evaluation processes including self-efficacy and shame as time varying covariates. A total of 71 young adults (Mage = 21.25, SD = 1.18; 55% male) reported moderate physical activity, exercise self-efficacy, and anticipated shame toward exercise once a week for five weeks. Latent growth curve models showed that a linear slope fit these data better than alternative models. Parameters of the linear model revealed that these young adults reported engaging in 40 minutes of moderate PA approximately three days per week. However, there were physical activity differences in initial levels and rates of change. Exercise self-efficacy consistently predicted physical activity in a positive direction and with a small-to-medium magnitude. Anticipated shame was an inconsistent predictor of physical activity, showing a negative direction and small magnitude at time one and on average across the five weeks. These findings highlight considerable variability in young adults’ short-term trajectories of physical activity and underscore both positive and negative processes of exercise related self-evaluations. Future physical activity interventions targeting young adults should incorporate strategies that enhance self-efficacy (e.g., mastery experiences) and reduce feelings of shame (e.g., attribution training).